The New World ant parasitoid genus Orasema (Hymenoptera: Eucharitidae) - Baker, Austin J.; Heraty, John M. (Zootaxa, 2020)
A key is provided to 16 recognized species groups, plus several species not assigned to species group, of Orasema Cameron (Eucharitidae), a widespread New World genus of myrmicine ant (Formicidae: Myrmicinae) parasitoids ranging from northern Argentina to southern Canada. Eight of the species groups are revised, of which five are newly established; keys are given to the species of each treated group, 22 species are newly described, and detailed life histories of several well-documented species are discussed. Revised are the Orasema coloradensis group (four species: O. coloradensis Wheeler, O. iridescens n. sp., O. scaura n. sp., and O. violacea Ashmead), the Orasema bakeri group (six species: O. bablyi n. sp., O. bakeri Gahan, O. dubitata n. sp., O. polymyrmex n. sp., O. taii Chien & Heraty, and O. texana Gahan), the Orasema tolteca group (two species: O. castilloae n. sp. and O. tolteca Mann), the Orasema sixaolae group (newly established, with four species: O. brachycephala n. sp., O. nebula n. sp., O. sixaolae Wheeler & Wheeler, and O. tinalandia n. sp.), the Orasema acuminata group (newly established, with two species: O. acuminata n. sp. and O. cerulea n. sp.), the Orasema peraltai group (newly established, with two species: O. chrysozona n. sp. and O. peraltai n. sp.), the Orasema johnsoni group (newly established, with two species: O. johnsoni n. sp. and O. spyrogaster n. sp.), and the Orasema heacoxi group (newly established, with two species: O. heacoxi n. sp. and O. masonicki n. sp.). Newly described or treated species not placed to species group are O. brasiliensis (Bréthes), O. cirrhocnemis n. sp., O. monstrosa n. sp., O. mutata n. sp., O. psarops n. sp., and O. roppai n. sp. Species concepts and relationships are based on morphology and a recently published molecular phylogeny.